Effects of a program of cervical cancer screening promotion for risk women at Selaphum District in Roi-Et Province - Sonsri, Suwimol; Iemsawasdikul, Warinee; Phothisapsuk, Chuenjit (Thai Journal of Nursing, 2021)
The objective of this quasi-experimental research was to find effects of a program of cervical cancer screening promotion based on the health belief model for risk women at Selaphum District in Roi-Et Province. The sample comprised 62 women at risk for cervical cancer, aged 30-60 years old, married, who had no cervical cancer screening within the past 5 years. They were selected by the purposive sampling technique as inclusion criterias. The research tools were a program of cervical cancer screening promotion and a questionnaire with 3 parts: (1) general data, (2) perception about cervical cancer with content validity index 1.0 and reliability coefficient 0.86, and (3) intention of going in for cervical cancer screening. Data were analyzed by descriptive statistics, t-test, Wilcoxon matched pairs signed - rank test and Z test. The results found as follows. (1) After the experiment, the experimental group had significantly higher perception about cervical cancer, perceived susceptibility, perceived severity, and perceived benefits of cervical cancer screening than before the experiment and that of the comparison group, and significantly lower perceived barriers of cervical cancer screening than before the experiment and that of the comparison group (p < .05); and (2) after the experiment, women in the experimental group who had intention of going in for cervical cancer screening were more than those in the comparison group (p < .05).